Pendidikan Kewirausahaan, Lingkungan Keluarga, Motivasi Berwirausaha dan Pengaruhnya Terhadap Intensi Berwirausaha Mahasiswa - Nur Allizah Rio Tiyanti; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aim of this research is to analyze the influence of variables (X1) entrepreneurship education, (X2) family environment, (X3) entrepereneurial motivation on (Y) students’ entrepeneurial intentions. The type of research used is a quantitative method with descriptive analysis. The data collection technique was carried out by distributing questionnaires using a Likert scale of one to five. The total sample was 134 respondents with the criteria being students who were/had studied entrepeneurship education. Entrepreneurship education. The data analysis techniques used in this research are: Outer Model with calcculations of Convergent Reliability, Discriminant Validity, Composite Realibility, Cronbach’s Alpha and Inner Model with calculations of T statistics, R-Square, f-Square, VIP and Path Coefficient using SmartPLS tools (Partial Least Square) version 4.0.9.3. The research results show that: (X1) Entrepreneurship education has positive and significant effect on students’ entrepreneurial intentions (Y). (X2) The family environment has a positive and significant effect on students’ entrepreneurial motivation has a positive and significant effect on students’ entrepreneurial intentions (Y). Recommendations for future researchers are to use other variables such as income expecctation variables and so on